Agreements in Online Loans and Consumer Legal Protection in Online Loan Services in Indonesia - Hardyansah, Rommy; Darmawan, Didit; Negara, Dharma Setiawan (JURNAL AKTA, 2025)
The rapid development of online lending services in Indonesia has a positive impact on the economy, but it also poses challenges related to legal aspects. This research aims to examine how agreements in online loans are regulated in Indonesian positive law and to analyze the legal protection provided to consumers of online loan services. This research uses normative legal research methods by analyzing various laws and regulations, legal doctrines, and relevant theories. The main focus of the research is to explore the regulation of online loan agreements, which still face various problems related to the unclear rights and obligations of the parties and the lack of transparency of information provided by service providers. In addition, this research also identifies problems related to consumer legal protection, especially in terms of supervision, misuse of personal data, and dispute resolution mechanisms that are still not optimal. The results show that although there are regulations from the Financial Services Authority (OJK), there are still many gaps that must be improved, both in the regulation of agreements and consumer protection. Therefore, this study is important to provide a deeper understanding of the role of law to maintain a balance between the development of the online lending sector and the protection of consumer rights.